Nonlinear dispersive waves and fluids : AMS Special Session on Spectral Calculus and Quasilinear Partial Differential Equations, and PDE Analysis on Fluid Flows, January 5-6, 2017, Atlanta, Georgia - Zheng, Shijun; Beceanu, Marius; Bona, J. L.; Chen, Geng, 1980-; Phan, Tuoc (Tuoc Van); Soffer, Avy (Avraham) (Contemporary mathematics (American Mathematical Society), 2019)
This volume contains the proceedings of the AMS Special Session on Spectral Calculus and Quasilinear Partial Differential Equations and the AMS Special Session on PDE Analysis on Fluid Flows, which were held in January 2017 in Atlanta, Georgia. These two sessions shared the underlying theme of the analysis aspect of evolutionary PDEs and mathematical physics. The articles address the latest trends and perspectives in the area of nonlinear dispersive equations and fluid flows. The topics mainly focus on using state-of-the-art methods and techniques to investigate problems of depth and richness.